The Cambridge companion to Jung - Dawson, Terence; Young-Eisendrath, Polly (Cambridge University Press, 1997)
This volume of specially commissioned essays is a critical introduction to the psychology of Carl Jung, one of the founders of psychoanalysis. Jung broke with Freud and developed his own theories which he called 'analytical psychology'. The essays set Jung in the context of his own time, outline the practice and theory of Jungian psychology and show how Jungians continue to question and evolve his thinking to fit the post-modern, multi-cultural world of contemporary psychoanalysis. Andrew Samuels's introduction gives an appreciation of Jung's work and discusses the three approaches to analytical psychology. The Companion includes a full chronology of his life and work, reading lists, a case study and a glossary. It is an indispensible reference tool for beginning students and specialists, written by an international team of Jungian analysts and scholars from various disciplines.